2013
DOI: 10.4103/0253-7613.108319
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir induced Fanconi syndrome: A possible pharmacokinetic interaction

Abstract: Tenofovir was introduced as a second line drug for the treatment of human immunodeficiency virus (HIV) infection in India in December 2009. Although rare, renal toxicity is a recognized adverse drug reaction (ADR) of this drug, especially when administered with boosted lopinavir-ritonavir. In this case, an HIV positive patient receiving tenofovir based antiretroviral therapy (ART) for last 1 year developed albuminuria, glycosuria and hypophosphatemia. Renal function tests and random blood sugar were within nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This presentation is similar to prior published cases. 1012 Nephrogenic diabetes insipidus was probable with the patient’s hypernatraemia and dehydration, evidenced by clinical exam and hemoconcentration on laboratory studies. Furthermore, there was no use of diuretics, history of poor access to water intake with insensible losses, or any reason to suspect central diabetes insipidus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This presentation is similar to prior published cases. 1012 Nephrogenic diabetes insipidus was probable with the patient’s hypernatraemia and dehydration, evidenced by clinical exam and hemoconcentration on laboratory studies. Furthermore, there was no use of diuretics, history of poor access to water intake with insensible losses, or any reason to suspect central diabetes insipidus.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] The cases reviewed make it clear that discontinuation of the drug is paramount and usually leads to overall improvement in all aspects of renal function. [3][4][5][6][7][10][11][12] Although our patient's baseline renal function wasn't recorded, it can be assumed that her renal impairment was attributed to the effects of tenofovir as it improved substantially after the treatment was discontinued. Several studies have shown that TDF is associated with either AKI or chronic kidney disease through proximal tubal injury, either tubular necrosis or interstitial nephritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of the thiazolidin-4-one scafold is gaining considrable attention due to the fact that its derivatives have shown a wide spectrum of activities. Thiazolidine-4-ones are important building blocks in pharmaceutical agent and biologically active products [1][2][3][4][5] . Several substituted thiazolidinones have been found to possess hypnotic, anaesthetic, sedative, anticonvulsant and microbiological activities [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%